Implementasi Revitalisasi Di Tapman Pendidikan Al-Qur’an Al-Huda Desa Talang Tinggi Kabupaten Seluma Barat - Febriyan, Recha; Dinata, Suvino; Viani, Riski Avta; Rizqia, Saqofa Washillatul; Komalasari, Yuningsih; Wahyuni, Seri; Kusmitasari, Resi; Harahap, Ade Ihwani; Novita, Helen; Manurung, Mely Navatilova (Pakis Journal Institute, 2024)
The Real Work Lecture activities carried out by the Fatmawati Sukarno Bengkulu State Islamic University were carried out by teaching local children. The service activities are located in Talang Tinggi Village, West Seluma Regency. The aim of carrying out this activity is to provide a positive influence on society, especially children in the field of religion. Children as the nation's next generation must need religious guidance. The current condition of the Al-Quran Education Park in Talang Tinggi Village is that learning is no longer active. This creates a problem for children who can no longer study the Koran. The first activity is carried out by conducting a review regarding the place for learning, then carrying out an analysis regarding needs in order to overcome the problems that occur. Second, apply all the work programs that have been created in order to achieve the expected goals. Third, make a report regarding the program that has been implemented. During the activity, it was carried out through observation and questions and answers to various related parties in order to produce accurate information. The results obtained after the revitalization of the Al-Huda Al-Qur'an Education Park are that it can foster children's desire to recite the Koran at TPQ so that they can increase their understanding in studying the Al-Qur'an.